Determinants of international reserves among Organisation of Petroleum Exporting Countries (OPEC) - Oladejo Tokunbo Bada; Kehinde Adekunle Adetiloye; Felicia Omowunmi Olokoyo; Grace Ukporhe (Comparative Economic Research. Central and Eastern Europe, 2022)
Member countries of the Organisation of Petroleum Exporting Countries (OPEC) are always in the news regarding the prices and supply of crude oil to the international market. One of the economic reasons for this is liquidity and the desire to accumulate international reserves by the respective countries. This paper examined the determinants of international reserves among the cartel against the backdrop of the motives for keeping reserves. With data from 2005 to 2018, the adopted variables that were tested with the system of generalised methods of moments (Sy-GMM) are inflation, exchange rates, oil prices, crude oil dependence, economic crises and others. The results and outputs show that inflation was negatively impactful externally and internally, while FDI inflows recorded negative significance. Economic crises and economic openness were positively significant, while oil prices and exchange rates were not significant determinants of international reserves accumulation. The paper recommends the maximisation of opportunities available by members during economic crises to accumulate reserves that will enable them to diversify from dependence on crude oil exports to include other products and a higher level of openness to open the economy up for competition to make the economies stronger.
Keywords: F14; F23; F31; F41; F43; 330; rnational reserves; Organisation of Petroleum Exporting Countries; crude oil prices; exchange rates; international trade